Novel technique to engineer aluminum profile at nickel-silicide/silicon: carbon interface for contact resistance reduction, and integration in strained N-MOSFETs with silicon-carbon stressors - Koh, S.-M. (2014)
10.1109/IEDM.2011.6131681